2013
DOI: 10.1111/ejn.12145
|View full text |Cite
|
Sign up to set email alerts
|

Role of a novel nociceptor autocrine mechanism in chronic pain

Abstract: We have previously shown, in the rat, that neuropathic and inflammatory events produce a neuroplastic change in nociceptor function whereby a subsequent exposure to a proinflammatory mediator (e.g. prostaglandin E2 ; PGE2 ) produces markedly prolonged mechanical hyperalgesia. While the initial approximately 30 min of this prolonged PGE2 hyperalgesia remains PKA-dependent, it subsequently switches to become dependent on protein kinase C epsilon (PKCε). In this study we tested the hypothesis that the delayed ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 67 publications
3
54
0
Order By: Relevance
“…Treatment with ODN against integrin β1 was started 11 days later, at which time ψεRACK-induced mechanical hyperalgesia had resolved (Fig. 1A) and, then, after 3 consecutive daily injections, testing for priming was performed by intradermal injection of the A1 adenosine receptor agonist CPA 15 . Of note, we have previously shown that, although intradermal injection of CPA does not induce changes in the mechanical threshold in non-primed animals, following priming it produces prolonged PKCε-dependent mechanical hyperalgesia 15 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Treatment with ODN against integrin β1 was started 11 days later, at which time ψεRACK-induced mechanical hyperalgesia had resolved (Fig. 1A) and, then, after 3 consecutive daily injections, testing for priming was performed by intradermal injection of the A1 adenosine receptor agonist CPA 15 . Of note, we have previously shown that, although intradermal injection of CPA does not induce changes in the mechanical threshold in non-primed animals, following priming it produces prolonged PKCε-dependent mechanical hyperalgesia 15 .…”
Section: Resultsmentioning
confidence: 99%
“…1A) and, then, after 3 consecutive daily injections, testing for priming was performed by intradermal injection of the A1 adenosine receptor agonist CPA 15 . Of note, we have previously shown that, although intradermal injection of CPA does not induce changes in the mechanical threshold in non-primed animals, following priming it produces prolonged PKCε-dependent mechanical hyperalgesia 15 . We observed that, when rats previously primed with ψεRACK, 2 weeks before, and treated with ODN-AS or MM for integrin β1 mRNA for 3 days, received injection of CPA on the dorsum of the hind paw, hyperalgesia developed only in the group treated with MM, showing that the expression of priming (i.e., the CPA-induced hyperalgesia) is integrin β1 dependent (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations